1994
DOI: 10.1007/bf00873087
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interrelationships of proteolyticClostridium botulinum types A, B, and F and other members of theClostridium botulinum complex as revealed by small-subunit rRNA gene sequences

Abstract: The phylogenetic interrelationships of members of the Clostridium botulinum complex of species was investigated by direct sequencing of their 16S rRNA genes. Comparative analysis of the 16S rRNA sequences demonstrated the presence of four phylogenetically distinct lineages corresponding to: i) proteolytic C. botulinum types A, B, and F, and C. sporogenes, ii) saccharolytic types B, E and F, iii) types C and D and C. novyi type A, and iv) type G and C. subterminale. The phylogenetic groupings obtained from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
39
0
4

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 22 publications
9
39
0
4
Order By: Relevance
“…C. botulinum strains were all in the low %G+C group I, and were separated into groups I-A, I-F and I-H based on rRNA homologies (Johnson & Francis, 1975). Further 16S rRNA analyses of the genus Clostridium confirmed the classification of C. botulinum into four groupings which corresponded to the four physiological groups, I to IV Hutson et al, 1993aHutson et al, , 1993b). An analysis of 174 C. botulinum strains by amplified fragment length polymorphism (AFLP) and by sequencing of 16S rRNA and BoNT genes confirmed the existence of at least four distinct genomic backgrounds, each of which has likely independently acquired BoNT genes through horizontal gene transfer (Hill et al, 2007).…”
Section: Introductionmentioning
confidence: 79%
“…C. botulinum strains were all in the low %G+C group I, and were separated into groups I-A, I-F and I-H based on rRNA homologies (Johnson & Francis, 1975). Further 16S rRNA analyses of the genus Clostridium confirmed the classification of C. botulinum into four groupings which corresponded to the four physiological groups, I to IV Hutson et al, 1993aHutson et al, , 1993b). An analysis of 174 C. botulinum strains by amplified fragment length polymorphism (AFLP) and by sequencing of 16S rRNA and BoNT genes confirmed the existence of at least four distinct genomic backgrounds, each of which has likely independently acquired BoNT genes through horizontal gene transfer (Hill et al, 2007).…”
Section: Introductionmentioning
confidence: 79%
“…If phylogenetic data are to be used as the basis for future taxonomic restructuring of the genus Clostridium, it is imperative that as many species as possible be sequenced and that the branching patterns of trees be resolved with confidence, In recent years there has been considerable progress toward this end, with complete (or nearly complete) 16s rRNA sequences available for more than 80 clostridial species (5,19,20,27,29,30,34,35,37,38,50). In this paper we describe the 16s rRNA gene sequences of an additional 34 clostridial strains and the results of a comparative sequence analysis and thereby provide an almost complete picture of the genealogical interrelationships in the genus.…”
mentioning
confidence: 99%
“…In more recent years, the application of 16S rRNA sequencing technology has unequivocally demonstrated that the four groupings are composed of distinct species. In the case of those groups important to human botulism, Group I strains, regardless of toxin type, are highly related to one another (99.7%-100% 16S rRNA sequence identity) and together with C. sporogenes form a single phylogenetic unit (Hutson et al 1993b). Neurotoxin-forming Group II strains (and their nontoxinogenic counterparts) form a distinct line that is quite separate from other saccharolytic clostridia and phylogenetically far removed from the Group I strains (Hutson et al 1993a).…”
mentioning
confidence: 99%